A high-performance flexible solid-state supercapacitor based on Li-ion intercalation into tunnel-structure iron sulfide. (20th November 2016) - Javed, Muhammad Sufyan; Jiang, Zhiqiang; Zhang, Cuiling; Chen, Lin; Hu, Chenguo; Gu, Xiao
Graphical abstract: The nanoparticle-aggregation spheres offer large specific area and easy ion diffusion paths, which greatly enhances the active sites for redox reaction on the surface. FeS2 network structure of the octahedrons with tunnels along c direction could provide diffusion paths for the Li + ion intercalation/de-intercalation during the charging/discharging process. Highlights: FeS2 nanospheres assembled by nanoparticles provide large specific area and easy ion transmission paths. First principles calculations are performed to investigate the diffusion mechanism of lithium ions in FeS2 . FeS2 network structure of the octahedrons and tunnels along c direction could benefit to ion intercalation. A flexible solid state supercapacitor based on FeS2 nanospheres shows highly capacitive behavior. Three charged supercapacitors connected in series can light 12 green color LED's for 5.5 min. Abstract: A flexible solid-state supercapacitor based on iron sulfide (FeS2 ) nanospheres supported on carbon-paper is fabricated, which exhibits excellent electrochemical performance such as, high capacitance of 484 F g −1 at a scan rate of 5 m Vs −1, good rate capability, and excellent cycling stability (95.7% after 5000 cycles). The supercapacitor achieves high energy density of 44 Wh kg −1 at power density of 175 W kg −1 with high coulombic efficiency (97%). Three charged supercapacitors connected in series can power 12 green-color light-emitting-diodes (LED, 3.0 V, 20 mA) for 5.5 minutes. To understand the detailed electrochemistry, we have carried out both experimental and theoretical investigations. The pseudocapacitive characteristics of the FeS2 nanospheres are systematically investigated by a single electrode in aqueous electrolyte. According to our structural analysis, the FeS2 nanospheres have orthorhombic structure, where Fe atoms are surrounded by 6 S atoms to form a FeS6 octahedron. These octahedrons are connected to form a network structure, which provide tunnels (2.55 × 4.77 Å). With all the evidence, we believe that the FeS2 nanospheres could be a promising material for supercapacitor electrodes.